Murder in a time of crisis: a qualitative exploration of the 2020 homicide spike through offender interviews - Densley, James A. (Journal of crime and justice, 2025)
This study investigates how the COVID-19 pandemic and the civil unrest following George Floyd’s murder influenced the 2020 homicide surge, focusing on individuals already at high risk for violence. Based on life history interviews with 18 people convicted of homicide in Minnesota, the research explores how the disruptions of 2020 intensified pre-existing vulnerabilities, accelerating pathways to lethal violence. Participants reported that the breakdown of social order, loss of routine, and economic instability created conditions that rapidly escalated violence within their lives and communities. This qualitative analysis complements existing quantitative research by offering a detailed account of the micro-level experiences behind the homicide spike, revealing how large-scale societal disruptions can shape individual trajectories toward serious violence. Findings underscore the need for policies that address structural inequalities and ensure continuity of social supports and mental health services during periods of widespread upheaval to prevent future escalations in violence.